USING QF-PCR ASSAY IN DETECTION OF COMMON GENETIC CAUSES IN INFERTILE MALES - Tai Nguyen, Cao Thi; Kien, Nguyen Trung; Bich Lien, Trinh Thi; Nhuan, Vu Thi; Vieng, Nguyen Chung; Khoa, Nguyen Dac; Vinh, Nguyen Phan; Bich Ngoc, Nguyen Thi; Thiet, Trinh Minh; Binh, Cao Luong; Khuon, Nguyen Van (Vietnam Journal of Biotechnology, 2018)
At present, quantitative fluorescent - polymerase chain reaction (QF-PCR) technology is widely being used in prenatal diagnosis of some common genetic syndromes such as Down syndrome, Patau syndrome and Edwards syndrome. The advantages of this technique are its high accuracy, rapid test results and wide applicability. It has used this technique to detect AZF (Azoospermia factor) micro-deletions by Devyser's kit at Tu Du Hospital, Ho Chi Minh City. The novelty of the study was to create a kit with 14 genetic markers and to develop a QF-PCR protocol to detect some common genetic causes in men seeking medical for their infertility with the sperm concentration of ≤ 5 million/ml. We conducted an evaluation in reliability in order to confirm whether the QF-PCR results from the set-up protocol were accurate and reliable. We developed the research on the application of QF-PCR to test for the DNA samples of patients. They were 10 normal reproductive men, 2 patients with Klinefelter syndrome, 4 patients with AZFc micro-deletions, 1 female with normal reproduction. Cordially, we used a sample of water to control the experiment. The results have shown that the kit with 14 genetic markers and the built-in QF-PCR protocol for detecting some common genetic causes in men seeking medical care for their infertility were accurate 100% compared to multiplex-PCR and peripheral blood lymphocyte cultures. The study results are important for identifying some common genetic causes in men seeking medical care for their infertility and helping doctors build the most inferior treatment regimens for their patients.